Marketing Mix in Team Sports in Serbia - Radenko M. Matic; Nebojsa Maksimovic; Jovan Vukovic; Dusan Corilic; Rajko Bujkovic; Damjan Jaksic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
Marketing activities, i.e. promotional presentations of various offers to a wide audience, represent inevitable means in strategic plans of organisations from various fields. Such approach also demands from sports organisations to form a promotional marketing mix. The objective of this paper was to examine the marketing mix in sports clubs of sports teams at the highest competition ranking in Serbia. A sample of 118 examinees - available managers from four collective sports management teams (football, basketball, handball and volleyball), was used for conducting an assessment of attitudes regarding the use of the marketing mix. Obtained results show a low current status of marketing in the assessed sports, and by implementing the Kruskal Wallis and Man Whitney tests, differences in certain elements of the marketing mix were also recognised. These differences indicate the advantage on the side of the managers working in football and basketball field as opposed to those working with handball and volleyball. Ultimately, theoretical and practical values of the obtained results were also discussed.